Distinct von Hippel-Lindau gene and hypoxia-regulated alterations in gene and protein expression patterns of renal cell carcinoma and their effects on metabolism - Leisz, Sandra; Schulz, Kristin; Erb, Susanne; Oefner, Peter; Dettmer, Katja; Mougiakakos, Dimitrios; Wang, Ena; Marincola, Francesco M.; Stehle, Franziska; Seliger, Barbara (Oncotarget, 2015)
During the last decade the knowledge about the molecular mechanisms of the cellular adaption to hypoxia and the function of the "von Hippel Lindau" (VHL) protein in renal cell carcinoma (RCC) has increased, but there exists little information about the overlap and differences in gene/protein expression of both processes. Therefore the aim of this study was to dissect VHL- and hypoxia-regulated alterations in the metabolism of human RCC using ome-based strategies. The effect of the VHL- and hypoxia-regulated altered gene/protein expression pattern on the cellular metabolism was analyzed by determination of glucose uptake, lactate secretion, extracellular pH, lactate dehydrogenase activity, amino acid content and ATP levels. By employing VHL-/VHL+ RCC cells cultured under normoxic and hypoxic conditions, VHL-dependent, HIF-dependent as well as VHL-/HIF-independent alterations in the gene and protein expression patterns were identified and further validated in other RCC cell lines. The genes/proteins differentially expressed under these distinct conditions were mainly involved in the cellular metabolism, which was accompanied by an altered metabolism as well as changes in the abundance of amino acids in VHL-deficient cells. In conclusion, the study reveals similarities, but also differences in the genes and proteins controlled by VHL functionality and hypoxia thereby demonstrating differences in the metabolic switch of RCC under these conditions.
EVALuna2:25711